From Private to Public: Using Authentic Audiences to Support Undergraduate Students’ Learning and Engagement - Hamilton, Erica; Han, Mihyun (Teaching and Learning Inquiry, 2024)
The purpose of this article is to explore the use of authentic audiences in higher education to support undergraduate learning. To explore the results of integrating authentic audiences in higher education, we present a collective case study in which the use of authentic audiences was employed in separate undergraduate courses at two different higher education institutions in the Eastern and Midwestern United States (N = 75). In one case, Wikipedia was employed as an authentic audience and in the other case, experienced secondary educators as well as Twitter were embedded. The goal of implementing authentic audiences in both settings and courses was to increase student engagement and foster critical thinking. Results suggest that integrating authentic audiences through these means can enhance undergraduate students’ engagement and learning and may serve to capture, but not necessarily foster, students’ critical thinking. Concurrently, an instructor’s pedagogy must also align with tenets associated with authentic audiences, including a commitment to a co-construction of knowledge and the purposeful selection of authentic audiences who are engaged, willing to partner, and have the necessary expertise and resources to contribute to students’ learning. Read the corresponding ISSOTL blog post here.